Storage Vessels as Indicators of Crisis Management. (2nd January 2022) - Bechar, Shlomit; Yasur-Landau, Assaf; Marom, Nimrod
Abstract : This article assesses the distribution of storage vessels, pithoi and jars in an effort to evaluate surplus management strategies connected to political and environmental conditions in the southern Levant in the second millennium BCE. We examined 27 ceramic assemblages from four Middle Bronze–Late Bronze sites in northern Israel: two rural sites (Tel Qashish and Tel Yoqneʾam) and two urban centres (Tel Hazor and Tel Beth-Shean). We then examined how variability in storage activity relates to major historical, political and climate changes recorded in the Levant within the chronological framework of the study. Our results suggest that the relative frequency of storage vessels varies according to type of settlement, is somewhat impacted by political events, and is weakly related to climatic events. This highlights the potential importance of focusing upon datasets that quantify the response of societies to political and climatic change as a measure of the latter's effect on the past. The results also allow us to suggest a change in the distribution system of Bronze Age urban centres.